Diversification of Shallots (Brama Powder) in Community Service Program - Wismaningsih, Endah Retnani; Susilowati, Indah; Zuliana, Ni’matu; Nurkhalim, Ratna Frenty; Ulilalbab, Arya; Putri, Elvanda Helzalia; Khoir, Ana Miftahul; Pawarti, Rona; Kurniawati, Nurul Istiqomah; Mukminati, Ana Zahratul; Arnawa, Gini Driya; Almahabbah, Fakihuddin; Hagarini, Pasha Aurischa (Media Karya Kesehatan, 2025)
This community service program aims to increase the added value and competitiveness of shallots through the innovation of BRAMA shallot powder (Brambang Mama) as a signature product of Karangsemi Village, Gondang District, Nganjuk Regency. The main problem faced by the community is the fluctuating price of shallots, particularly during harvest seasons, which leads to decreased income for farmers. The method consisted of collecting gender-disaggregated data, coordinating with the village government and the SAPA MAMA group, conducting intensive training on processing shallots into powder, packaging and branding techniques, and providing technical assistance in production technology. The results show that participants were able to produce high-quality shallot powder with a distinctive taste and aroma, as well as attractive packaging. BRAMA was agreed upon as a flagship village product to be marketed through UMKM, village bazaars, and sub-district-level promotion. This program had a positive impact by improving community skills, utilizing local potential, and creating sustainable business opportunities. Further training on packaging design, business management, PIRT and halal certification, as well as digital marketing strategies is recommended to strengthen BRAMA as a culinary identity of Nganjuk and to support the village’s economic resilience.Keywords: Shallot; Community empowerment; Village flagship product; BRAMA powder